2016
DOI: 10.7554/elife.12735
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of CpG frequencies in influenza A genome attenuates pathogenicity but enhances host response to infection

Abstract: Previously, we demonstrated that frequencies of CpG and UpA dinucleotides profoundly influence the replication ability of echovirus 7 (Tulloch et al., 2014). Here, we show that that influenza A virus (IAV) with maximised frequencies of these dinucleotides in segment 5 showed comparable attenuation in cell culture compared to unmodified virus and a permuted control (CDLR). Attenuation was also manifested in vivo, with 10-100 fold reduced viral loads in lungs of mice infected with 200PFU of CpG-high and UpA-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(157 citation statements)
references
References 40 publications
13
144
0
Order By: Relevance
“…In addition, the dinucleotide frequency has been shown to change following cross-species transmission events, such as the marked decrease in CpG frequency as influenza A virus jumps from birds to humans (20,21). Studies of influenza viruses and picornaviruses indicate that the innate immune response might recognize RNA-specific CpG motifs, such that the suppression of CpG in viruses could assist immune evasion (22)(23)(24). In contrast, other studies have suggested that dinucleotide bias in viruses simply reflects background mutation pressure.…”
Section: Abstract Dinucleotide Bias Evolutionmentioning
confidence: 99%
“…In addition, the dinucleotide frequency has been shown to change following cross-species transmission events, such as the marked decrease in CpG frequency as influenza A virus jumps from birds to humans (20,21). Studies of influenza viruses and picornaviruses indicate that the innate immune response might recognize RNA-specific CpG motifs, such that the suppression of CpG in viruses could assist immune evasion (22)(23)(24). In contrast, other studies have suggested that dinucleotide bias in viruses simply reflects background mutation pressure.…”
Section: Abstract Dinucleotide Bias Evolutionmentioning
confidence: 99%
“…However, experimental use of kinase inhibitors reverted the attenuation phenotype of the mutants, suggesting a role for an unknown PRR in mediating a dinucleotide usage-specific immune response [24]. In a follow-up study on influenza virus, the authors demonstrated that, despite marked attenuation of replication, virus mutants enriched in CpG and UpA induced higher inflammatory cytokines and adaptive responses in vivo [25].…”
Section: Detection Of Specific Sequencesmentioning
confidence: 99%
“…IN: Integrase. Table 1 Interactions between viral sequence patterns and innate immune pathways deciphered by large-scale synonymous recoding of viral genomes Virus Sequence pattern studied Innate immune pathway involved Reference Influenza (A/U)CG(A/U) IFN-I secretion, TLR7-dependent [23] Simian Immunodeficiency Virus Nucleotide bias IFN-I, IRF3-dependent [28] Echovirus CpG and UpA Unknown PRR, IRF3-independent [24] Infuenza CpG and UpA Pro-inflammatory cytokines Unknown PRR [25].…”
Section: Figure 2 a Role For Microbial Sensing Pathways In Detectingmentioning
confidence: 99%
“…It was discovered that codon and codon pair deoptimization of vertebrate viruses not only increases the number of codons, or codon pairs that are underrepresented in coding sequences of the host, but also increases the frequency of CpG and, to lesser degree, TpA (UpA) dinucleotides in recoded sequences [45,54,55,58]. The increase of CpG and TpA dinucleotides by codon pair deoptimization is inadvertent, as codon pairs that contain CpG and TpA dinucleotides at the codon pair boundary (NNC-p-GNN) are among the most underrepresented codon pairs in vertebrates [45,55].…”
Section: Codon and Codon Pair Deoptimization Increases The Number Of mentioning
confidence: 99%
“…A subsequent study from the same group demonstrated that elevation of CpG frequencies in influenza A virus can also result in moderate attenuation of the virus in vitro and in vivo [58]. However, since recoded viruses with increased CpG or UpA frequencies did not have the same codon bias as the control-unmodified and permuted-viruses, changes in the codon bias could confound observed viral properties.…”
Section: Virus Attenuation By Increase Of Cpg/tpa Dinucleotides Frequmentioning
confidence: 99%